Determinates of smallholder small grain (sorghum, pearl millet and rapoko) farmer market participation and choice of marketing outlets: a case of Maranda, ward 9, Mwenezi, Masvingo province - Makotose, Taidaishe L. (Midlands State University, 2019)
Markets are crucial for agricultural growth and transformation. Following the persistent climatic changes in Zimbabwe farmers in Agro ecological region III, IV and V have been encouraged to grow small grains as a diversification coping strategy. Smallholder famer’s access to profitable markets is vital so as to improve commercialization of small grain (sorghum, millet, rapoko) farming in Zimbabwe. This study therefore seeks to determine the factors influencing small grain smallholder farmers marketing outlets, choice of marketing outlets and the impact of post-harvest management on market participation in Maranda, district, ward 9 Mwenezi .The cross sectional data were collected from a sample of 94 households using the snowballing sampling technique. STATA 11 statistical package was used to analyze data. Descriptive statistics on the characteristics of small holder farmers were done and it was found that the results showed that the 69.15% females were the major participants in small grain marketing outlets compared to their counter parts. Multinomial logistic regression model was used to determine the factors influencing small grain small holder farmers marketing outlet choice using .Marginal effects were then used to interpret data. The study found out that sources of price information and also the payment procedures have a significant effect to the marketing outlets farmers do not prefer to sell their output at GMB, because they have got the wrong information from the co farmers who are the major source of information .Post harvest management do have a significant effect on market participation because farmers have poor storage infrastructure and also the storage costs exceeds the production costs. At the end the farmers end up selling their grains early after harvest with aims to reduce storage costs. There is need to profile farmers on the basis of production, spatial location and education level and encourage them to participant in marketing profitable marketing outlets.